1996
DOI: 10.1518/001872096778827206
|View full text |Cite
|
Sign up to set email alerts
|

SPECIAL SECTION: Task Complexity in Emergency Medical Care and Its Implications for Team Coordination

Abstract: To elicit components of task complexity in emergency medical care, a study was conducted to contrast one medical procedure with two levels of task urgency in trauma patient resuscitation. Videotapes of actual resuscitation were reviewed to extract task characteristics of the procedure. Two levels of urgency were compared in the following areas: patient status, technical difficulty of tasks, the amount of available patient monitoring information, and the pace of work. Four components of task complexity in emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(60 citation statements)
references
References 20 publications
0
59
0
1
Order By: Relevance
“…This is due in part to expert groups such as the Institute of Medicine and regulators like the Joint Commission for Accreditation of Health-care Organizations who advocate some type of team training. In addition, research suggests the need for improved teamwork and communication in neonatal intensive care, 2,3,16 emergency departments, 10 the operating room, 17,18 trauma resuscitation [19][20][21] and among residents of all disciplines. 22 Despite this interest and research, two recent reviews concluded that no studies have shown that team training can improve teamwork and the quality of care, 11,12 and a cluster randomized trial of team training for labor and delivery teams did not find significant changes in the process of care or outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…This is due in part to expert groups such as the Institute of Medicine and regulators like the Joint Commission for Accreditation of Health-care Organizations who advocate some type of team training. In addition, research suggests the need for improved teamwork and communication in neonatal intensive care, 2,3,16 emergency departments, 10 the operating room, 17,18 trauma resuscitation [19][20][21] and among residents of all disciplines. 22 Despite this interest and research, two recent reviews concluded that no studies have shown that team training can improve teamwork and the quality of care, 11,12 and a cluster randomized trial of team training for labor and delivery teams did not find significant changes in the process of care or outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…Salas, Stagl, Burke, & Goodwin's (2007) review of the literature identified over 130 models and frameworks for team performance that range in level of specificity. While some models are generalizable and parsimonious, such as Salas, Sim's, and Burke's (2005) "Big Five" of teamwork, other models are much more task-or context-specific (for example Xiao, Hunter, Mackenzie, Jefferies, & Horst, 1996). Other models focus on specific team functions or processes .…”
Section: Team Performance Models and Taxonomiesmentioning
confidence: 99%
“…In surgery, human factors analysis has been used to analyze errors and near misses during neonatal cardiac operations [47,48]. Human factors analysis has also been used to examine an activity (e.g., an operation) in terms of its components such as technical and nontechnical skill demands [28], mental workload [49], interactions with technology [50] and the work environment [28], and team dynamics [51]. Using this framework for identifying and classifying errors may allow for a better understanding of why near misses and errors occur so as to develop preventive strategies.…”
Section: Human Factors Researchmentioning
confidence: 99%